Effectiveness and Safety of Pyrotinib, and Association of Biomarker With Progression-Free Survival in Patients With HER2-Positive Metastatic Breast Cancer: A Real-World, Multicentre Analysis - Chen, Qitong; Ouyang, Dengjie; Anwar, Munawar; Xie, Ning; Wang, Shouman; Fan, Peizhi; Qian, Liyuan; Chen, Gannong; Zhou, Enxiang; Guo, Lei; Gu, Xiaowen; Ding, Boni; et al. (Frontiers in Oncology, 2020)
Background: Pyrotinib, an irreversible pan-ERBB inhibitor, has shown promising antitumour activity and acceptable tolerability. This research was conducted to evaluate the actual use and effectiveness of pyrotinib in China, therefore, contributed to solve the problem of real-world data scarcity. Methods: In this retrospective study, 168 patients who received pyrotinib treatment for HER2-positive metastatic breast cancer (MBC) in Hunan Province from June 2018 to August 2019 were included. Progression-free survival (PFS), tumour mutation burden (TMB), and drug-related adverse events (AEs) after pyrotinib administration were analysed. Results: The median PFS (mPFS) time in the 168 participants was 8.07 months. The mPFS times in patients with pyrotinib in second-line therapy (n = 65) and third-or-higher-line therapy (n = 94) were 8.10 months and 7.60 months, respectively. Patients with brain metastases achieved 8.80 months mPFS time. In patients with pyrotinib in third-or-higher-line therapy, patients who had previously used lapatinib still got efficacy but showed a shorter mPFS time (6.43 months) than patients who had not (8.37 months). TMB was measured in 28 patients, K-M curve (P = 0.0024) and Multivariate Cox analysis (P = 0.0176) showed a significant negative association between TMB and PFS. Diarrhoea occurred in 98.2% of participants (in any grade) and 19.6% in grade 3–4 AEs. Conclusion: Pyrotinib is highly beneficial to second-or-higher-line patients or HER2-positive MBC patients with brain metastases. Pyrotinib seems to be a feasible strategy both in combination of chemotherapeutic drugs or as a replacement of lapatinib if diseases progressed. TMB could be a potential predictor for evaluating pyrotinib’s effectiveness in HER2-positive MBC.